Gray Whale (Eschrichtius robustus) Health and Disease: Review and Future Directions - Stimmelmayr, Raphaela; Gulland, Frances M. D. (Frontiers in Marine Science, 2020)
The eastern North Pacific gray whale (Eschrichtius robustus) population is considered “recovered” since the days of commercial whaling, with a population of over 25,000 animals. However, gray whale habitat is changing rapidly due to urbanization of the migratory coastal corridor, increases in shipping, and climate change altering water conditions and prey distribution. Increased single strandings and intermittent large-scale mortality events have occurred over the past 20 years, raising questions about how gray whale health is affected by whale population size (density dependence), climate change, and coastal development. To understand the impacts of these factors on health and the role of health changes in whale population dynamics, increased understanding of the pathogenesis and epidemiology of diseases in gray whales is needed. To date, most information on gray whale health and disease is in single case reports, in sections of larger papers on whale ecology, or in technical memoranda and conference proceedings. Here we review existing data on gray whale health and disease to provide a synthesis of available information and a baseline for future studies, and suggest priorities for future study of gray whale health. The latter include nutritional studies to distinguish annual physiological fasting from starvation leading to mortality, identification of endemic and novel viruses through increased use of molecular techniques, quantifying parasitic infections to explore interactions among prey shifts and parasite infection and body condition, as well as enhancing necropsy efforts to identify stochastic causes of mortality such as vessel strikes, entanglements, and predation. Integration of health and disease studies on individual animals with population monitoring and models of whale/prey dynamics will require interdisciplinary approaches to understand the role of health changes in population dynamics of this coastal whale.